Day of tears : a novel in dialogue - Lester, Julius (Jump at the Sun/Hyperion Books for Children, 2005)
Presents an historical fiction written in first-person format that follows Emma, the slave of Pierce Butler, through a series of events in her life as her master hosts the largest slave auction in American history in Savannah, Georgia in 1859 in order to pay off his mounting gambling debts.